2021
DOI: 10.1007/s00125-020-05368-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved transition to adult care in youth with type 1 diabetes: a pragmatic clinical trial

Abstract: Aims/hypothesis Youth with type 1 diabetes are at high risk for loss to follow-up during the transition from paediatric to adult diabetes care. Our aim was to assess the effect of a communication technology enhanced transition coordinator intervention compared with usual care on clinic attendance among transitioning youth with type 1 diabetes.Methods In this open label, pragmatic clinical trial of youth with type 1 diabetes, aged 17-18 years, transitioning from paediatric to adult diabetes care, the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…29 Yet other novel transition programs including transition coordinators, such as in Canada and Australia, have shown mixed results in terms of successful transfer to adult care and improvement in acute type 1 diabetesrelated outcomes, but none specifically assessed reduction in youth-reported anxiety. [30][31][32] Although a transition coordinator may help bridge the gap between paediatric and adult healthcare teams, our participants also highlighted that having family or friends who had previously transferred care helped to ease anxiety during the transition process, thereby illustrating the positive influence of peers. Other studies have also noted the desire from preand post-transition individuals for shared experiences and guidance from others with type 1 diabetes during the transition process 33 as well as reduced anxiety in emerging adults engaged in a type 1 diabetes-specific peer support group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29 Yet other novel transition programs including transition coordinators, such as in Canada and Australia, have shown mixed results in terms of successful transfer to adult care and improvement in acute type 1 diabetesrelated outcomes, but none specifically assessed reduction in youth-reported anxiety. [30][31][32] Although a transition coordinator may help bridge the gap between paediatric and adult healthcare teams, our participants also highlighted that having family or friends who had previously transferred care helped to ease anxiety during the transition process, thereby illustrating the positive influence of peers. Other studies have also noted the desire from preand post-transition individuals for shared experiences and guidance from others with type 1 diabetes during the transition process 33 as well as reduced anxiety in emerging adults engaged in a type 1 diabetes-specific peer support group.…”
Section: Discussionmentioning
confidence: 97%
“…Physician continuity after transfer to adult care has been shown to reduce the risk of diabetes‐related hospitalizations, 7 and in another study from Israel, a dedicated transition clinic, including both paediatric and adult endocrinologists and a transition coordinator, improved follow‐up rates and glycaemic control 29 . Yet other novel transition programs including transition coordinators, such as in Canada and Australia, have shown mixed results in terms of successful transfer to adult care and improvement in acute type 1 diabetes–related outcomes, but none specifically assessed reduction in youth‐reported anxiety 30–32 . Although a transition coordinator may help bridge the gap between paediatric and adult healthcare teams, our participants also highlighted that having family or friends who had previously transferred care helped to ease anxiety during the transition process, thereby illustrating the positive influence of peers.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore read with interest the results of the pragmatic clinical trial by Butalia et al [3], which reported a reduction in absolute losses to follow-up in a cohort of young adults with type 1 diabetes who were exposed to a communication technology enhanced transition coordinator. The intervention was associated with a fourfold reduction in absolute disengagement from specialist medical services in the first 12 months post-transition, compared with a historical cohort [3]. This paper adds to the transition literature base, but a robust process of evaluation would allow understanding of the factors that would facilitate roll out of this intervention at scale.…”
mentioning
confidence: 99%
“…This is particularly important given that it is difficult to interpret the relative benefit of individual elements within multifaceted interventions. Combined medical and nonmedical appointment attendance was included as an outcome measure in this study [3], but detail around the timing of these appointments (same day or otherwise) is not provided, and therefore it is unclear how attendance was truly affected by transition coordination. Considering that intervention participants are reported to have had a mean of 1.4 HbA 1c measurements over 5.8 attendances in the 12 months following transition [3], it may be assumed that participants were seen by multiple members of the multidisciplinary team on each of 2 separate attendances for physician review.…”
mentioning
confidence: 99%
See 1 more Smart Citation